The human stain - Roth, Philip (New York : Vintage International, 2001)
Coleman Silk, a distinguished professor at a small New England college where he has managed over the course of fifty years to make a lot of enemies, experiences a sort of personal liberation when he is forced from his job on false claims of racism -- a charge made all the more ironic due to a secret Silk has been keeping nearly his entire life.
Wilson's Fiction, October 2010
Library Journal, March 2000
Booklist starred, March 2000
Pub Weekly, March 2000
Kirkus Starred, March 2000
New York Times, May 2000
Keywords: Passing (Identity) -- Fiction; African American men -- Fiction; College teachers -- Fiction; Newark (N.J.) -- Fiction; Jewish men -- Fiction; Passing (Identity) -- Fiction; African American men -- Fiction; Colleges and universities -- Faculty -- Fiction; Newark (N.J.) -- Fiction; Jewish men -- Fiction; Psychological fiction; Psychological fiction